2018
DOI: 10.1111/joim.12728
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations and mechanisms of myocardial lipotoxicity in obesity

Abstract: Environmental and socioeconomic changes over the past thirty years have contributed to a dramatic rise in the worldwide prevalence of obesity. Heart disease is amongst the most serious health risks of obesity, with increases in both atherosclerotic coronary heart disease and heart failure among obese individuals. In this review, we focus on primary myocardial alterations in obesity that include hypertrophic remodelling and diastolic dysfunction. Obesityassociated perturbations in myocardial and systemic lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
1
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 129 publications
0
66
1
18
Order By: Relevance
“…In addition, emerging evidence also shows ER stress has a major role in the progression of cardiac lipotoxicity . For in vitro studies, palmitate treatment in NRCMs decreased cell viability and induced ER stress‐mediated apoptosis, which was attenuated by exogenous CTRP9 in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, emerging evidence also shows ER stress has a major role in the progression of cardiac lipotoxicity . For in vitro studies, palmitate treatment in NRCMs decreased cell viability and induced ER stress‐mediated apoptosis, which was attenuated by exogenous CTRP9 in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, emerging evidence also shows ER stress has a major role in the progression of cardiac lipotoxicity. 8,9 For in vitro studies, palmitate treatment in NRCMs decreased cell viability and induced ER stress-mediated apoptosis, which was attenuated by exogenous CTRP9 in a dose-dependent manner. Furthermore, we demonstrated that CTRP9 deficiency exacerbated HFD-induced ER stress-related F I G U R E 7 AMPK phosphorylation is weakened in HFD-fed CTRP9 knockout mice and palmitate-treated NRCMs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that the duration of fasting may be a stress, and will need to be carefully titrated depending upon the species (as 24 hours of fasting in a mouse is perhaps equivalent to a much longer period of fast in humans given differences in lifespan). Obesity and diabetes induce a plethora of myocardial changes that culminate in a clinically observed entity of diabetic cardiomyopathy (93) which is characterized by myocardial lipid overload (200). Whether these beneficial effects of intermittent fasting are also observed in the diabetic myocardium and are the subject of active investigation.…”
Section: Benefits Of Intermittent Fasting In Animal Models On Cardiommentioning
confidence: 99%